MSG07: An International Cohort Study Comparing Epidemiology and Outcomes of Patients With Cryptococcus neoformans or Cryptococcus gattii Infections. (27th March 2021) - Baddley, John W; Chen, Sharon C-A; Huisingh, Carrie; Benedict, Kaitlin; DeBess, Emilio E; Galanis, Eleni; Jackson, Brendan R; MacDougall, Laura; Marsden-Haug, Nicola; Oltean, Hanna; Perfect, John R; Phillips, Peter; et al.
Abstract: Background: Cryptococcosis due to Cr yptococcus neoformans and Cryptococcus gattii varies with geographic region, populations affected, disease manifestations, and severity of infection, which impact treatment. Methods: We developed a retrospective cohort of patients diagnosed with culture-proven cryptococcosis during 1995–2013 from 5 centers in North America and Australia. We compared underlying diseases, clinical manifestations, treatment, and outcomes in patients with C. gattii or C. neoformans infection. Results: A total of 709 patients (452 C. neoformans; 257 C. gattii ) were identified. Mean age was 50.2 years; 61.4% were male; and 52.3% were white. Time to diagnosis was prolonged in C. gattii patients compared with C. neoformans (mean, 52.2 vs 36.0 days; P  < .003), and there was a higher proportion of C. gattii patients without underlying disease (40.5% vs 10.2%; P  < .0001). Overall, 59% had central nervous system (CNS) infection, with lung (42.5%) and blood (24.5%) being common sites. Pulmonary infection was more common in patients with C. gattii than in those with C. neoformans (60.7% vs 32.1%; P  < .0001). CNS or blood infections were more common in C. neoformans –infected patients ( P  ≤ .0001 for both). Treatment of CNS disease with induction therapy of amphotericin B and flucytosine occurred in 76.4% of patients. Crude 12-month mortality was higher in patients with C. neoformans (28.4% vs 20.2%; odds ratio, 1.56 [95% confidence interval, 1.08–2.26]). Conclusions: This study emphasizes differences in species-specific epidemiology and outcomes of patients with cryptococcosis, including underlying diseases, site of infection, and mortality. Species identification in patients with cryptococcosis is necessary to discern epidemiologic patterns, guide treatment regimens, and predict clinical progression and outcomes. Abstract : This large study emphasizes differences in species-specific epidemiology of patients with cryptococcosis, including underlying diseases, site of infection, and mortality. Species identification in patients with cryptococcosis is important to discern epidemiologic patterns, guide treatment regimens, and predict clinical progression and outcomes.